PENGARUH VARIASI KONSENTRSAI LARUTAN KOH TERHADAP UNJUK KERJA ELEKTROLISER TIPE WET CELL - Ikhsaniyusuf Alfiansyah Putra; Moch. Dhofir; Lunde Ardhenta (Jurnal Mahasiswa TEUB, 2022)
This study uses a wet cell type HHO gas generator which was developed with the addition of PWM as a control of duty cycle, frequency, and voltage. The duty cycle in PWM is set at 75% and the frequency is set at 1 kHz. The electrodes used are made of grade A graphite with dimensions of W x W x H: 14 cm x 2 cm x 2 cm. The catalyst used was KOH with variations of 10 grams, 15 grams, and 20 grams dissolved in 1 L of distilled water. Each test was carried out with a pure DC source and with a PWM source for a period of 15 minutes for each test. Parameters measured in the test are voltage, current, temperature, and volume of HHO gas. Meanwhile, what is calculated is the power needed by the HHO generator and the efficiency of the HHO generator. The results obtained in this study were the average volume of the highest HHO gas was 94.67 ml/minute when using a pure DC source and 20 grams of KOH. The smallest power consumption is 33.90 - 41.25 Watt when using a PWM and 10 gram KOH source. The highest efficiency is 21.95% when using a 20 gram PWM and KOH source.Keywords: HHO gas, Pulse